Implementasi Program Pemagangan dalam Negeri Pada Dinas Tenaga Kerja dan Transmigrasi Provinsi Kepulauan Riau - Suryanti Nengsih, Neng; Usman Siam, Nurbaiti; Sujono, Agus; Choiroel, Didyk; Kurniawati, Chandra (STISIPOL Raja Haji, 2024)
The increasing unemployment is a result of the instability of the economic structure, which has made it difficult to develop employment opportunities. On the other hand, the lack of competence in the Asean Economic Community has led to an increase in the number of job seekers, both within the country and from other neighboring countries. To overcome this, workforce competency must be increased, including an apprenticeship program that passes competency tests held by the National Professional Certification Agency (BNSP). The aim of this research is to determine the implementation of the Domestic Apprenticeship Program of the Riau Islands Manpower and Transmigration Service. Researchers use qualitative methods and descriptive approaches to analyze data according to this type of research, namely descriptive. The results of this research are that the Riau Islands Province has been able to show that the quality of apprenticeship participants after participating in the Apprenticeship Program is able or ready to compete in the world of work. The advice given in this research is that the government and the business world coordinate more frequently regarding domestic apprenticeship program activities in order to find solutions regarding the quality and workforce needs needed by the business world and the industrial world today in order to compete with graduates from outside the Riau Islands Province.